Internet hand x-rays: A comparison of joint space narrowing and erosion scores (Sharp/Genant) of plain versus digitized x-rays in rheumatoid arthritis patients - Watson Margaret M; Cabarrus Luis P; Montgomery Gregory P; Arbillaga Hector O; Martin Liam; Edworthy Steven M (BMC Musculoskeletal Disorders, 2002)
Abstract Background The objective of the study is to examine the reliability of erosion and joint space narrowing scores derived from hand x-rays posted on the Internet compared to scores derived from original plain x-rays. Methods Left and right x-rays of the hands of 36 patients were first digitized and then posted in standard fashion to a secure Internet website. Both the plain and Internet x-rays were scored for erosions and joint space narrowing using the Sharp/Genant method. All scoring was completed in a blind and randomized manner. Agreement between plain and Internet x-ray scores was calculated using Lin's concordance correlations and Bland-Altman graphical representation. Results Erosion scores for plain x-rays showed almost perfect concordance with x-rays read on the Internet (concordance 0.887). However, joint space narrowing scores were only "fair" (concordance 0.365). Global scores demonstrated substantial concordance between plain and Internet readings (concordance 0.769). Hand x-rays with less disease involvement showed a tendency to be scored higher on the Internet versions than those with greater disease involvement. This was primarily evident in the joint space narrowing scores. Conclusions The Internet represents a valid medium for displaying and scoring hand x-rays of patients with RA. Higher scores from the Internet version may be related to better viewing conditions on the computer screen relative to the plain x-ray viewing, which did not include magnifying lens or bright light. The capability to view high quality x-rays on the Internet has the potential to facilitate information sharing, education, and encourage collaborative studies.